Detectability and Persistence of Cyclospora cayetanensis Oocysts in Artificially Contaminated Soil and Fresh Herbs Grown Under Controlled Climatic Conditions - Ellie L. Rogers; Joseph Arida; John Grocholl; Joyce Njoroge; Sonia Almeria (Pathogens)
Cyclospora oocysts are thought to be highly resistant in the environment but the climatic factors which determine the presence/persistence of Cyclospora oocysts are currently unknown. The main objective of this study was to determine the effects of temperature, water content, and soil texture on C. cayetanensis detection/persistence in artificially contaminated soil and herbs grown under controlled environmental conditions. Soil and leaves of three potted herbs (cilantro, parsley, and basil) grown in growth chambers and inoculated with C. cayetanensis oocysts were collected at 7, 14, 21, 28–31, 35–38, 42–45, 49–52, and 56 days post inoculation (dpi). Under wet watering conditions, independent of temperature, positive C. cayetanensis detection was observed at each sampling collection in both soil and herb leaves. Additionally, all three herbs were found to be positive for the parasite throughout the study duration in arid watering conditions. Conversely, short-lived persistence in soil was observed under arid conditions independent of temperature in Sandy Clay Loam soil (up to 14 dpi) and in Silt Loam soil (up to 21 dpi). Our results on the effect of desiccation on the presence and persistence of oocysts may provide useful insights for the proper cleaning and sanitizing of utensils or food contact surfaces to help control the persistence of the parasite.